PELATIHAN PENGGUNAAN INSTRUMEN IDENTIFIKASI KESULITAN FUNGSIONAL BELAJAR SISWA MENGGUNAKAN APLIKASI KOBOTOOLBOX BAGI GURU SDN 21 CAKRANEGARA - Widodo, Arif; Affandi, Lalu Hamdian; Indraswati, Dyah; Umar, Umar; Hidayati, Vivi Rachmatul (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
The identification process is the earliest step in the service stages for children with learning functional difficulties. Knowledge and skills about the identification process must be owned by the teacher. A teacher must have the ability to identify children who are suspected of having learning difficulties. This ability is important for teachers to have in providing appropriate learning services to students who experience functional learning difficulties. The results of observations in several partner schools found a problem that the knowledge and skills of teachers in identifying children with learning difficulties were still lacking. Based on these problems, it is necessary to make efforts to increase the knowledge and skills of teachers in identifying children with functional learning difficulties. The solution offered to overcome this problem is to conduct Training on the Use of Functional Difficulty Identification Instruments for Student Learning Using the Kobo toolbox Application for elementary school teachers. Through this training, it is hoped that it will increase the knowledge and skills of teachers in identifying children with learning difficulties.